2004
DOI: 10.1111/j.1440-1797.2003.00236.x
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde scavenging from peritoneal dialysis solutions using reduced aminothiol compounds

Abstract: Scavenging with aminothiol compounds masked the destructive carbonyl group (C = O) of formaldehyde and formed a compound that has antioxidant properties. The addition of aminothiol compounds may improve the biocompatibility of commercial PD solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…It is important, for the above-mentioned reasons, to perform successful removal of benzaldehyde from the solvent mixture before any side reactions will occur. The screening procedure for obtaining a suitable scavenging technology for benzaldehyde was initially performed with amines [17][18][19][20][21][22][23][24], inorganic salts [25], organic acids and their anhydrides [19]. The most desired option was found to be tris(hydroxymethyl)aminomethane (TRIS), which converts carbonyl compounds into oxazolidines [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It is important, for the above-mentioned reasons, to perform successful removal of benzaldehyde from the solvent mixture before any side reactions will occur. The screening procedure for obtaining a suitable scavenging technology for benzaldehyde was initially performed with amines [17][18][19][20][21][22][23][24], inorganic salts [25], organic acids and their anhydrides [19]. The most desired option was found to be tris(hydroxymethyl)aminomethane (TRIS), which converts carbonyl compounds into oxazolidines [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Aldehydes are associated with increased cellular injury and may contribute to peritoneal membrane damage among patients treated with PD. 27 In our study, the range of formaldehyde concentrations that induced apoptosis of HPMCs was found to be 30–500 µM, as determined by MTT assays. Legge and Thorell reported the concentration of formaldehyde in PD solution between 6 and 15 µM.…”
Section: Discussionmentioning
confidence: 49%
“…Confluent hPMC were quiesced with serum‐free M199 for 1 h prior to the measurement of Ca 2+ i (intracellular calcium). Cells cultured in plastic flasks were harvested using 0.025% trypsin:0.01% EDTA and resuspended in KRS (Krebs—Ringer solution) (Bird et al, 1994). The number of cells used for each experiment was corrected to 4.0×10 4 cells/ml.…”
Section: Methodsmentioning
confidence: 99%
“…The number of cells used for each experiment was corrected to 4.0×10 4 cells/ml. The hPMCs were loaded with 2.0 μmol/l Fura‐2 acetoxymethylester for 30 min at 37°C, based on previously published methods (Bird et al, 1994). Fura‐2‐loaded cells were resuspended in 2 ml of buffered KRS containing 1.0 mmol/l Ca 2+ and transferred to a 3‐ml silica cuvette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation